Large area electrochromics for architectural applications - Mathew, J.Gordon H.; Sapers, Steven P.; Cumbo, Michael J.; O'Brien, Nada A.; Sargent, Robert B.; Raksha, Vladimir P.; Lahaderne, Robert B.; Hichwa, Bryant P. (Journal of non-crystalline solids, 1997)
Electrochromic (EC) devices suitable for large area architectural applications require a minimum acceptable performance in depth of color, switching time, chromatism and durability to be viable. In this paper we discuss these minimum needs and present performance data on various devices that meet or exceed most of these requirements with neutral coloration and depth of color > 10:1. These devices have demonstrated repeatable performance for > 20 000 cycles.